Meeting the challenges of a changing World: the annual report on the work of the organization - United Nations (New York, 2006)
In this, Kofi A. Annan's tenth and last Annual Report as Secretary General, he seeks to provide an overview of the Organization's main achievements and challenges during the previous twelve months in the light of the critical developments in the decade since he took office. He has also subsumed in a single report both the work of the Organization as such and the progress made in implementing the Millennium Declaration, which in previous years had been the subject of a separate report
Keywords: United Nations Organizations